Vamos a ayudar! - Ring, Susan; Ramos, Gloria (Bloomington, Minn. : Red Brick Learning : Capstone Press, 2006)
Describes various ways that people can help eachother in a community.
Includes index.
Keywords: Community development -- Juvenile literature; Spanish language materials; Bilingual books -- Spanish and English; Spanish language -- Children's books; Community development